2019
DOI: 10.1177/1556984519827703
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Totally Endoscopic Coronary Artery Bypass Grafting: Systematic Review of Clinical Outcomes from the Past two Decades

Abstract: Robotic totally endoscopic coronary artery bypass grafting (TECAB) was introduced in 1998 and has over a period of two decades gradually emerged from single-vessel revascularization to multivessel bypass grafting. Dedicated centers have continuously evolved and further developed this minimally invasive method of coronary bypass surgery. A literature review was conducted to assess intra- and postoperative outcomes of TECAB. PubMed returned 19 comprehensive articles on TECAB. Investigation was focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Concerning learning curves similar to the MIDCAB procedure a triple digit number of repetitions is necessary for the individual surgeon and the team to achieve a good comfort level (79,80). For conversion a learning curve for the whole community of robotic heart surgeons has been described recently (81). Conversion rates affected almost one out of two patients in the early 2000s but nicely fell below 5% over the last years.…”
Section: Commentmentioning
confidence: 99%
“…Concerning learning curves similar to the MIDCAB procedure a triple digit number of repetitions is necessary for the individual surgeon and the team to achieve a good comfort level (79,80). For conversion a learning curve for the whole community of robotic heart surgeons has been described recently (81). Conversion rates affected almost one out of two patients in the early 2000s but nicely fell below 5% over the last years.…”
Section: Commentmentioning
confidence: 99%
“…They also provide a natural platform for the use of multiple arterial grafts and bilateral inflows in many patients, which is increasingly important as the evidence supporting improved long‐term survival accumulates 82 . In addition to a sternotomy‐based approach, anOPCAB can also be achieved using minimally invasive direct coronary artery bypass (MID‐CAB) 83 and totally endoscopic techniques (TECAB) with robotic assistance 84,85 in suitable patients.…”
Section: From Reduction To Complete Avoidance Of Aortic Manipulation:mentioning
confidence: 99%
“…With newer technical advancements, there are improvements in conversion rates, operative time, and the impact of the learning curve on the outcome. 37 …”
Section: Totally Endoscopic Coronary Artery Bypassmentioning
confidence: 99%
“… 38 Similar clinical outcomes were noted in recent systematic reviews by Göbölös and Cao. 37 , 39 Göbölös and colleagues analyzed a total of 2,397 TECAB cases with less than half being multivessel procedures. That study demonstrated an acceptable rate of perioperative mortality (0.8%) and perioperative major events such as stroke (1%), renal failure (1.6%), de novo atrial fibrillation (13.3%), and operative revision rate due to postoperative hemorrhage (4.2%).…”
Section: Totally Endoscopic Coronary Artery Bypassmentioning
confidence: 99%
See 1 more Smart Citation